ACTIVATING PRIOR KNOWLEDGE: THE IMPACT OF PRE-READING TASKS ON READING PROFICIENCY (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article explores the critical role of pre-reading activities in fostering effective reading comprehension within language education. Challenging the notion that reading is a passive decoding process, the author argues that successful comprehension is a dynamic and strategic endeavor that begins before engagement with the text. Drawing on foundational theories and empirical research, the article outlines five key functions of pre-reading strategies: activating prior knowledge, fostering anticipation and intrinsic motivation, pre-teaching vocabulary and conceptual frameworks, establishing reading purposes, and developing metacognitive awareness. Through detailed examples and scholarly references, the author emphasizes that pre-reading tasks are not ancillary, but essential tools for enhancing reader engagement, comprehension, and long-term literacy development. The article concludes by advocating for the deliberate and consistent integration of pre-reading strategies in reading instruction to cultivate more strategic, confident, and independent readers.